Pengaruh Model Pembelajaran Teams Games Tournament Terhadap Kemampuan Shooting Sepakbola Siswa Kelas X - Edo Yahya Alfian; Ismaya, Bambang; Dermawan, Dikdik Fauzi (Universitas Hamzanwadi, 2024)
This study aims to examine the effect of the teams games tournaments learning model on the ability to shoot inside the foot. The method used is an experiment with a nonequivalent control group design. The population in this study were all students of class X SMAN 8 Tambun Selatan consisting of 9 classes and totaling 288 students. The sample in the study was selected using cluster random sampling technique. Data analysis techniques using SPSS are normality test, homogeneity test, hypothesis testing. The results of the pretest and posttest data analysis were carried out with the Paired Sample T-test hypothesis test. The conclusion of this study is that the results of the posttest value of each test instrument have the results of the Paired dample T-test test value with the “Test Statistic” output with a sig value. (2-tailed) < 0.05 (0.000 < 0.005), so the conclusion is that there is a significant effect of the results of giving treatment in the form of the teams games tournaments learning model on the ability to shoot soccer with the inside leg of class X students conducted at SMA Negeri 8 Tambun Selatan.